The Changamirian offshoots in South Africa: The case of the Valoyi of Limpopo Province - Mathebula, Mandla D. (HTS teologiese studies, 2020)
Several studies that have been conducted about the Changamire society fall short of fully explaining this ancient society’s direct impact on the current Southern African ethnological landscape. Although a number of studies conducted in South Africa, Botswana, Mozambique and Zimbabwe show various societies may have emerged from the Changamire, these studies rarely give a clear chronology regarding the emigrations from this ancient society. This article uses oral historical methodology to explore the migration history and some genealogy of the Valoyi of Limpopo as one of the Changamire offshoots in an attempt to give a lucid chronology of events pertaining to one of this ancient society’s traceable offshoots. Orla testimonies, conversations, anecdotes and interviews are used to collect oral data. Using oral accounts and available literature, the article outlines a movement of the Valoyi from the country of the Changamire in the present-day Zimbabwe to the present-day Mozambique and later to South Africa’s Limpopo Province, where they are currently found. Following latest trends in oral history, collected data are subjected to oral historical methodology, privileging the voice of the narrator. Collected voices are triangulated with other voices and available secondary data, although there are limited written sources available. By employing oral historical methodology, the study contributes to indigenous methodologies and narrative methods of data collection and analysis, mainstreaming neglected indigenous discourses and epistemologies.Contribution: This study broadens the debate on the role of oral history to document genealogical links within cross border historiography, especially documented fragmented communities separated by different colonial regimes.